Remote Sensor untuk Monitoring CO dan NO2 Terpublikasi Online - Rahmadani, Alfiandi Aulia Rahmadani; Setiawan, Budhy; Radianto, Donny (Jurnal Elektronika dan Otomasi Industri, 2024)
Air quality is important for the survival of the entire ecosystem. Air contains various substances, namely, CH4, PM2.5, NO2, SO2, CO, PM10, and so on. At certain levels these substances have the potential to cause health problems. This study discusses a remote sensor system using Wi-Fi communication on ESP32 and the Decision Tree Algorithm as a classification of values to the ISPU for CO and NO2 levels whose reading data is sent to the MySQL database server then the data is displayed on the website and on a 128x64 Graphic LCD. Based on the tests carried out the system runs according to plan, where the sensor can detect CO and NO2 by sampling per 5 seconds then the reading value will be classified using the Decision Tree Algorithm and the reading results will be sent to the database every 30 seconds and displayed on the website with a delivery delay of 5 seconds and data on the website can be downloaded in CSV format.